Persepsi Mahasiswa Akuntansi Mengenai Faktor-Faktor yang Mempengaruhi Pemilihan Karir - Eko Arief Sudaryono; Sri Rahayu; Doddy Setiawan (Jurnal Akuntansi dan Bisnis, 2006)
The aim of this research is to identifying student perception about factor that influences them to choose career. The samples were accounting students on the third year on the publics and private universities at Jakarta, Surakarta, and Yogyakarta. The results from Kruskal Wallis test shows that difference student perception about factors influencing career choices are financial reward, professional training, professional confession, work environment and demand from labor market. But they are indifference on social values and personality. Based on gender analysis the different student perception are financial reward, professional confession, social values, demand of labor market, and personality.